Flawed MoO2 belts transformed from MoO3 on a graphene template for the hydrogen evolution reaction1. Issue 16 (28th April 2015) - Wu, Longfei; Wang, Xinsheng; Sun, Yupeng; Liu, Yang; Li, Jinghong
<x xml:space="preserve">Abstract</x> A novel method to construct flawed MoO2 belts on graphene was developed, which provided an alternative way to develop highly efficient electrocatalysts.